Sequential patterns of students’ drawing in constructing scientific explanations: focusing on the interplay among three levels of pictorial representation - Park, Joonhyeong; Chang, Jina; Tang, Kok-Sing; Treagust, David; Won, Mihye (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.